Student Creativity in Creating Geogebra Applet for Quadratic Function Material - Karomah, Syarifatul; Siswono, Tatag Yuli Eko; Zulnaidi, Hutkemri (Universitas Negeri Surabaya, 2024)
This research aims to describe the creativity and creative process of students with high, medium, and low levels of creativity. This qualitative research involved 6 Senior High School students in grade XI, 2 students at each level of creativity. The data collection technique uses assignments to make Geogebra applets that are analyzed with document analysis methods and interviews related to students' creative processes that are analyzed with interactive models. The research results show that the Geogebra applets produced by students are different at each level. The higher the level, the Geogebra applets are the more complex in use of Geogebra tools, providing many elements of novelty from the examples given, relevant to the task, and effective in achieving the set goals. Furthermore, the student's creative process with the stages of synthesizing ideas, generating ideas, planning the ideas, and applying ideas at each level has a different process. High creativity students go through each creative process stage well and repeat several stages to produce the Geogebra applet as in the assignment. Meanwhile, students with medium and low creativity are not good at going through each stage of the creative process.